Characterization of innovative Pt-ceria catalysts for PEMFC by means of ex-situ and operando X-Ray Absorption Spectroscopy. (15th February 2022) - Pollastri, Simone; Bogar, Marco; Fiala, Roman; Amenitsch, Heinz; Yakovlev, Yurii; Lavacchi, Alessandro; Aquilanti, Giuliana; Matolin, Vladimir
Abstract: As the demand for energy is rising, the role of batteries and fuel cells in everyday life is undeniable, but fuel cell systems are still currently not employed worldwide mainly because of their cost, which is due to the large amount of Pt used in catalyst layers. Recently, it was demonstrated that catalysts composed by low Pt loading (around 10 μg/cm 2 ) onto ceria (CeOx ) matrix are a promising alternative, showing comparable performances with respect to catalysts made by Pt only. Indeed, a strong metal to support interaction between Pt and ceria has been already observed and exploited for application in direct methanol fuel cells. In this context, the aim of the present study is to investigate the stability of innovative Pt-CeOx anode catalyst deposited on two different supports and characterized by means of X-ray Absorption Spectroscopy (XAS). The XANES ex-situ data collected at the Ce L3 -edge highlighted the stability of ceria when directly deposited onto the nano-Gas Diffusion Layer (nGDL) whereas it is particularly unstable when deposited onto the so-called Carbon Ionomer Layer (CIL), where Ce was found irreversibly reduced to Ce 3+ upon contact with the air. These behaviors are confirmed also by preliminary test experiments conducted in operando conditions, using a modified fuel cell designed on purpose. In addition, EXAFS data collected ex-situ at the Pt L3 -edge evidenced an increase in the fraction of Pt 2+ as the overall amount of Pt (or the Pt/Ce ratio) is decreasing, in agreement with existing literature. Our results provide an extended picture about characterization of Pt-CeOx catalyst, focusing on the effects of the hosting support, in order to improve the fabrication of more stable Membrane Electrode Assemblies (MEAs) with low Pt contents to be employed with PEMFCs. Graphical abstract: The lower efficiency and stability of ptceO2 anode catalyst sputtered on carbon-lonomer-Layer has been linked to the quick reduction of Ce. Image 1 Highlights: 2 kind of Pt-ceria anode catalyst were prepared using a novel sputtering technique. Differences in the efficiency are visible in the first days of operation. Samples were studied both ex situ and in operando conditions through XAS and SAXS. When sputtered on Carbon Ionomer Layer, the catalyst is less stable. Pt 2+ fraction increases as the Pt/Ce ratio decreases.